2021
DOI: 10.3390/ani11061718
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomic Analysis of Chicken Gut Microbial Community, Function, and Resistome to Evaluate Noninvasive and Cecal Sampling Resources

Abstract: When conducting metagenomic analysis on gut microbiomes, there is no general consensus concerning the mode of sampling: non-contact (feces), noninvasive (rectal swabs), or cecal. This study aimed to determine the feasibility and comparative merits and disadvantages of using fecal samples or rectal swabs as a proxy for the cecal microbiome. Using broiler as a model, gut microbiomes were obtained from cecal, cloacal, and fecal samples and were characterized according to an analysis of the microbial community, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
(61 reference statements)
2
15
0
Order By: Relevance
“…They play a very important role in maintaining the relative stability of the poultry gastrointestinal tract and nutrient digestion and absorption ( Jiangrang, 2003 ; Ilina, 2016 ). The cecum is the most developed site of intestinal microorganisms in poultry ( Jianhua, 2010 ; Kang et al, 2021 ; Pedroso et al, 2021 ). However, studies have found that gut microbes form a mutualistic symbiosis with their hosts during a long process of coevolution.…”
Section: Discussionmentioning
confidence: 99%
“…They play a very important role in maintaining the relative stability of the poultry gastrointestinal tract and nutrient digestion and absorption ( Jiangrang, 2003 ; Ilina, 2016 ). The cecum is the most developed site of intestinal microorganisms in poultry ( Jianhua, 2010 ; Kang et al, 2021 ; Pedroso et al, 2021 ). However, studies have found that gut microbes form a mutualistic symbiosis with their hosts during a long process of coevolution.…”
Section: Discussionmentioning
confidence: 99%
“…Through 12 phyla of bacteria, represented analysis by highquality 16S rRNA gene sequences of chicken bacteria, the predominant bacteria were Firmicutes (almost 70% of sequences) and Bacteroidetes (12.3% of sequences) phyla, with cell densities exceeding 10 11 per g of digesta (58,59). Within the phylum Firmicutes, Clostridium, Ruminococcus, Lactobacillus, Eubacterium, and Fecalibacterium are the domain bacteria (60), while genera Bacteroides, Prevotella, Parabacteroides, and Alistipes are the domain bacteria in phylum Bacteroidetes (58). However, the composition of the intestinal microbiota can be altered by dietary manipulations and pathological environment (61).…”
Section: Gut Microbialmentioning
confidence: 99%
“…However, as described by Sklan and colleagues (1978) , these communities are connected, able to sow microbes and influence the microbiota throughout in the gastrointestinal tract. However, the functional activities of the sections of the intestine are quite different ( Huang et al, 2018 ; Rychlik, 2020 ; Yuan et al, 2020 ; Kang et al, 2021 ). The microbial functions in the hindgut have been well-documented, but in the foregut, to date, these functions of the microbiota and their relationship with gut function have received scant attention in the research literature which limits the understanding of the interplay between the gut microbiome and cellular functions.…”
Section: Gapsmentioning
confidence: 99%
“…Existing investigations in poultry have afforded a basic understanding of the impact of diet and feed supplements on the composition and activity of the gut microbiota in the hindgut, but not in the foregut, with a few exceptions ( Wen et al, 2019 ; Kang et al, 2021 ; Schekkers et al, 2021 ). However, currently, a detailed translational approach in applying diet as a tool to improve bird performance and health remains limited.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation